Videography BIG SET (Soundfactory, 2012)
Audio Recorder : Zoom H5 - 299 USDCameras : Canon EOS 60 (2 pieces) - 2757 USD (919 USD / piece) Lens 1 : Canon EF 100mm f2.oUSM - 415 USD Lens 2 : Sigma 10-20mm F3.5 EX DC HSM - 619 USD Lens 3 : Tamron 70-200mm f2.8 AF DI LD Macro - 499 USD